TRADISI REBU DALAM MASYARAKAT KARO: EKSISTENSI DAN PEMERTAHANAN IDENTITAS BUDAYA DI ERA GLOBALISASI - Annisa Suci Ardhini; Lestari Dara Cinta Utami Ginting; Muhammad Dafitra (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2024)
The Karo tribe, which inhabits the province of North Sumatra, has a variety of traditions and cultures, one of which is the Rebu Tradition. This tradition prohibits direct communication between in-laws and sons-in-law of different genders, as well as between in-laws of different genders. In the Karo language, "rebu" means abstinence or prohibition of an action. In the current era of globalization, where the culture of good manners is often overlooked, local traditions such as the Rebu Tradition face the risk of being forgotten. This research aims to explore the existence of Rebu Tradition in Karo society, particularly in Sukambayak Village, in the context of the globalization era. The historical method is used with the approaches of heuristics, criticism, interpretation, and historiography. The results showed that the Rebu Tradition is still strong in the lives of the Karo people in Sukambayak Village, despite being faced with globalization. This tradition is still upheld in various events and daily life